Experience of Pandemic Influenza A (H1N1) 2009 at Dhaka Medical College Hospital - Islam, Quazi Tarikul; Kahhar, Azizul; Arif, Syed Mohammad; Ahasan, HAM Nazmul; Siddiqui, Md Mahmudur Rahman; Mahbub, Md Shahriar; Kabir, Ahmedul; Arif, Khan Mohammad; Kibria, Golam; Saha, Narayan Chandra (Journal of Medicine, 2010)
Introduction: Bangladesh recorded the first case of 2009 pandemic influenza A (H1N1) virus infection on 18th June 2009. This report describes the clinical and epidemiological characteristics of both the indoor and outdoor patients reporting in Flu Ward and Flu Corner of Dhaka Medical College Hospital. Methods: This cross-sectional study was done on highly suspected 833 registered outdoor (flu corner) and 28 indoor patients admitted in Flu ward of Dhaka Medical College Hospital during the study period of August 2009 to November 2009. A suspected case was defined as an influenza-like illness and either a history of travel to a country where infection had been reported in the previous 7 days or an epidemiologic link to a person with confirmed or suspected infection in the previous 7 days. A confirmed case was defined by a positive real-time reverse-transcriptase polymerase chain reaction (RT-PCR) assay. Results: Most of the patients were in between 20 to 30 years age group. Indoor patients presented with mostly fever (92.85%), rhinorrhea (71.42%), shortness of breathe (89.28%) and cough (64.28%). Maximum duration of fever in indoor patients was 4 days. RT-PCR from throat swab sample for H1N1 tested positive in 9 (32.14%) indoor patients. Out of the 833 outdoor patients 596(71.54%) patients had fever, 585(70.22%) had cough, 410(49.21%) had rhinorrhea and 314(37.69%) had sore throat. Only 2(7.14%) admitted patients died of flu. Conclusion: Despite widespread infection mortality rate is quite low. Prompt implementation and adherence to national guidelines on 2009 pandemic influenza A (H1N1) should be encouraged. Keywords: Pandemic influenza A (H1N1); Dhaka Medical College Hospital; Bangladesh. DOI: 10.3329/jom.v11i2.5452 J MEDICINE 2010; 11 : 119-123